The interplay of (semiotic) technologies and genre: the case of the selfie. Issue 5 (20th October 2018) - Zhao, Sumin; Zappavigna, Michele
ABSTRACT: The selfie is one of the most widely publicized, criticized, and debated visual phenomena of our time. However, formulating a definition of the selfie is not straightforward, as visual clues – be they representational or compositional – alone are not sufficient for identification. Recognizing an image as a selfie, rather than a portrait, often requires viewers to interpret the image in relation to the technological and sociocutural context in which the photo was taken and shared. In this paper, we consider the technological conditions that have shaped the evolution of the selfie as a visual genre. Central to our discussion is the premise that the selfie is not simply a genre for self-representation, but means of generating various perspectives: that of the selfie maker, the represented visual participant, and the viewer identification. This unique perspective-generating affordance of the selfie is both facilitated and constrained by the various technologies involved in selfie practices. On the one hand, the technological and physical constraints of the smart phone camera give rise to a specific form of "distorted" look which makes certain types of selfie possible. On the other hand, social media platforms facilitate the sharing of selfies, which results in increasingly stylized and creative ways in which perspectives of the self can be represented, negotiated, and, in the case of selfies manipulated via apps, augmented.